Experimental investigation of non-ideality and non-adiabatic effects under high pressure releases. (14th December 2015) - Kuznetsov, M.; Pariset, S.; Friedrich, A.; Stern, G.; Travis, J.; Jordan, T.
Abstract: This paper presents experimental studies involving high pressure gaseous releases with specific attention to the non-adiabatic character of the process approaching cryogenic temperatures, especially when the influence of heat exchange with ambient air becomes important. A small-scale facility is designed and constructed to simulate the transient blow-down of a cryogenic fluid through a small break. Gaseous and liquid nitrogen were planned to be used as a surrogate material for GH2 and LH2. The experimental results complement the quasi-stationary safety regulation tests and provide time-dependent data for verification of the theoretical models. Different orifice sizes (0.5, 1, 2, 3, 4 mm) and initial vessel (over-) pressures 30–200 bar are used in the tests. The measured time-dependent data for vessel discharge pressure, thrust, discharge mass flow rate, and gas temperatures are compared with a theoretical model for high pressure nitrogen release. This verification for nitrogen also assures the equation of state for hydrogen, which is based on the same methodology. Graphical abstract: Highlights: A high-pressure nitrogen discharge at pressures 30–200 bar in a volume of 2.87 dm 3 . A comparison of measured pressure, thrust, mass flow, and temperature with theory. Non-adiabatic character of gas release due to heat losses from wall to cold gas. Measured pressure scaled using initial pressure, speed of sound, volume and nozzle area.